ChemInform Abstract: Synthesis of Quinoline‐Fused 1‐Benzazepines Through a Mannich‐Type Reaction of a C, N‐Bisnucleophile Generated from 2‐Aminobenzaldehyde and 2‐Methylindole. Issue 25 (June 2016) - Min, Lijun; Pan, Bin; Gu, Yanlong
Abstract: A variety of quinoline‐fused benzazepines are synthesized via Mannich‐type reactions of a C, N‐bisnucleophile such as (VII).